Age-related decline in interhemispheric transfer of tactile information: The fingertip cross-localization task. (July 2020) - Piccirilli, Massimo; D'Alessandro, Patrizia; Germani, Alessandro; Boccardi, Virginia; Pigliautile, Martina; Ancarani, Viola; Dioguardi, Maria Stefania
Highlights: The efficiency of hemispheric information transfer decreases significantly with age. Changes in hemispheric interaction contribute to cognitive dysfunction in old age. Normal aging should be considered an example of a disconnection syndrome. The fingertip localization test could be a reliable tool for monitoring brain aging. Abstract: According to the disconnection hypothesis of cognitive aging, cognitive deficits associated with brain aging could be a result of damage to connective fibres. It has been suggested that the age-related decline in cognitive abilities is accompanied by age-related changes in interhemispheric communication ensured by commissural fibres. This study aimed to contribute to this topic by investigating the effects of aging on the efficiency of interhemispheric transfer of tactile information. A total of 168 right-handed subjects, aged 20–90 years, have been tested using the fingertip cross-localization task: the subject must respond to a tactile stimulus presented to one hand using the ipsilateral (uncrossed condition) or contralateral hand (crossed condition). Because the crossed task requires interhemispheric transfer of information, the value of the difference between the uncrossed and crossed conditions (CUD) can be deemed to be a reliable measure of the efficiency of the interhemispheric interactions. The uncrossed condition was more accurate than the crossed condition for all ages. However, the degree of the CUD was significantly age-dependent. The effectiveness of the interhemispheric transfer of tactile information decreased significantly with age and may indicate the occurrence of age-related changes of the corpus callosum. Considerably, performance appears to decline around the seventh decade of life with the fastest decline in the subsequent decades. The results suggest a relationship between brain aging and the efficiency of the interhemispheric transfer of tactile information. The findings are discussed in relation to the strategic role of white matter integrity in preserving behavioural performances.